EVALUASI PRODUKSI OVERBURDEN DI PIT SMD2 PT. PAMAPERSADA NUSANTARA DISTRIK KIDECO JAYA AGUNG KALIMANTAN TIMUR - Citcy Tiurmaida Manullang; Juanita R. Horman (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2020)
Overburden is a top layer that usually covers the coal layer mined. This layer contains material that has no nutrients, and is usually structured by other various rock layers. Therefore, activities regarding excavation and loading of overburden is very important in order to obtain coal to be produced. In mining operation, it is necessary to evaluate overburden production in a certain period, so that it can be used to increase production in the next period, and to identify the problems occurred in the pit during production calculations. The results from the operation of a PC 3000 include 95% of PA, 50% of UA, 718.74 Bcm/day of productivity and 246,835.76 Bcm of actual production. According to the actual calculations in the SMD2 Pit, the production of PT. PAMA does not achieve target as planned, so a further analysis needed to be taken to assess the biggest cause of loss in the pit. The results highlight that the main parameters for the loss in the pit include rain, slippery, and waiting for equipment.